Restoration of Rumah Kutai Perak at KAED, IIUM, Gombak - Salleh, Nurul Hamiruddin (2018)
The talk is to share on a restoration project of Rumah Kutai Perak by Kulliyyah of Architecture & Environmental Design (KAED), International Islamic University Malaysia (IIUM). The project was begun in June 2017 and successfully completed in March 2018. The house is originally from Jalan Seputeh, Parit, Perak and believed to have been built in 1920. Its original owner was a village headman or chief. The house has Rumah Anjung measuring 2.76m x 4.52m with 16 columns and Rumah Ibu measuring 7.24m x 7.03m. This chengal wood-structured house also has a single room and kitchen house. All the house components were carefully dismantled at the original site before being repaired at the contractor workshop in Kuala Kangsar. After repaired, the house components were transported more than 200km to the new site at the IIUM Gombak’s campus. The house is a part of the KAED Malay Enclave Teaching Lab, a teaching laboratory for the students of KAED especially its architecture students. This project is also to help in preserving our traditional built heritage as well as promoting it to local and international visitors while visiting the university.